Scaling corrected lower limb girths in professional male soccer players from different divisions - Osorio Gutiérrez, A; Zúñiga Galaviz, U; Gómez Llanes, A; Toledo Domínguez, I; Favela Ramírez, C; Coelho-e-Silva, M. (Journal of Human Sport & Exercise, 2025)
This study examined the influence of height, bone lengths, and bone diameter on interindividual variability of the corrected thigh (CTG) and calf girth (CCG) in professional soccer players from the First Division, Under-20 (U-20), and Under-17 (U-17), using simple allometric models. Anthropometric data from 109 male players were collected, and a multistep analysis, including Pearson correlation and linear regression, was employed to identify predictor variables. The allometric modelling procedure proposed by Nevill et al. (1992) and Nevill & Holder (1994) was used to determine the best model that allowed for the adjustment of inter individual variability in CTG and CCG. The femur diameter was integrated into simple allometric models, elucidating 50% of the variability in both the CTG and CCG. Height, weight, CTG, and CCG exhibited variations, with first division players demonstrating elevated values. However, after adjusting for the femur diameter using the allometric model, most differences were neutralized. In conclusion, this study established femur biepicondylar diameter as the predominant predictor of CTG and CCG in professional football players (1st Division, U20, U17), and integrating this parameter into a simple allometric model successfully mitigated the impact of body size, enabling appropriate CTG and CCG comparisons within player divisions.